2017
DOI: 10.3389/fonc.2017.00055
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response: At the Intersection between Endoplasmic Reticulum Function and Mitochondrial Bioenergetics

Abstract: Endoplasmic reticulum (ER) to mitochondria communication has emerged in recent years as a signaling hub regulating cellular physiology with a relevant contribution to diseases including cancer and neurodegeneration. This functional integration is exerted through discrete interorganelle structures known as mitochondria-associated membranes (MAMs). At these domains, ER/mitochondria physically associate to dynamically adjust metabolic demands and the response to stress stimuli. Here, we provide a focused overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 63 publications
(75 reference statements)
2
28
0
Order By: Relevance
“…) and carry out important protein quality control activities such as the mitochondrial unfolded protein response (Carreras‐Sureda et al . ). Mitochondria are also an important site for production of reactive oxygen species important for signalling beneficial adaptations (Gonzalez‐Freire et al .…”
Section: Introductionmentioning
confidence: 97%
“…) and carry out important protein quality control activities such as the mitochondrial unfolded protein response (Carreras‐Sureda et al . ). Mitochondria are also an important site for production of reactive oxygen species important for signalling beneficial adaptations (Gonzalez‐Freire et al .…”
Section: Introductionmentioning
confidence: 97%
“…More recent studies have implicated specific mitochondrial-ER tethering proteins, such as FUNDC1, as having important roles in maintaining normal cardiac contractility in mice (64)(65)(66). Studies outside the cardiac context have shown that there are numerous components of the UPR ER that are associated with MAM structure and function, including ER chaperones, the IP 3 receptor and PERK, which, if deleted decreases calcium movement from the ER to mitochondria (67). Relatedly, PERK deletion in the heart disrupts calcium signaling in cardiac myocytes in mice, in vivo (68).…”
Section: Integrating Er and Mitochondrial Function In Cardiac Myocytesmentioning
confidence: 99%
“…Given that MFN2 is present on the ER membrane, it also regulates ER-mitochondria tethering (de Brito and Scorrano, 2008). This connection, known as ER mitochondria-associated membranes (MAMs), has been shown to play an essential role in the regulation of ER, mitochondrial, and cellular functions (Ngoh et al, 2012;Hamasaki et al, 2013;Schneeberger et al, 2013;Muñoz et al, 2014;Carreras-Sureda et al, 2017;Pathak and Trebak, 2018). MFN2 downregulation is associated with decreased expression of subunits of the Krebs cycle and electron transport chain, reduced oxygen consumption, lower DY m , and increased reactive oxygen species (ROS) (Santel and Fuller, 2001;Yasukawa et al, 2009;Ngoh et al, 2012;Wakai et al, 2014;Filadi et al, 2015;Schrepfer and Scorrano, 2016).…”
Section: Basic Aspects Of Mitochondriamentioning
confidence: 99%
“…These are linked with buffering of Ca +2 levels, innate immunity, apoptosis and biogenesis of iron-sulfur clusters (Yasukawa et al, 2009;Naon and Scorrano 2014;Stehling et al, 2014). Moreover, mitochondria closely interact with other organelles such as the endoplasmic reticulum (ER) and regulate several pathways in the cell (de Brito and Scorrano, 2009;Betz et al, 2013;Chen et al, 2014;Carreras-Sureda et al, 2017;Xu et al, 2017). As a result, perturbations in mitochondrial function may dramatically disturb cellular homeostasis, resulting in several common diseases in humans (Bach et al, 2003;Chen et al, 2007Chen et al, , 2010Schaefer et al, 2008;Misko et al, 2012;Schon et al, 2012;Sebastian et al, 2012;Eschbach et al, 2013;Payne et al, 2013;Schneeberger et al, 2013;Pareyson et al, 2015;Ramírez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%